Analyzing the impact of Social Interaction on Stock Market Participation: A Qualitative Study Using NVivo - Shrestha, Sajeeb Kumar; Karki, Tej Bahadur; Mahat, Dipak; Neupane, Dasarath (Nepal Journal of Multidisciplinary Research, 2024)
Background: Stock market participation plays a crucial role in wealth creation and economic welfare. Prior studies show social interaction factors like parental guidance, partner opinions and online networks can influence such financial decisions. However, little is known about their combined impact in developing markets. Methods: This study analyzed the influence of social interaction on stock market participation in Kathmandu Valley, Nepal. Qualitative data was collected through interviews of 10 investors and analyzed using NVivo software. Tools included word clouds, cluster analysis, sentiment analysis and thematic coding. Results: Results indicated that while parents generally lacked knowledge, some were influenced by participating relatives. Partners motivated research through information sharing and encouragement. Community reputation had a positive effect. Internet emerged as the dominant information source compared to offline relationships. Moderately positive sentiments were observed for community, partner and internet influences. Conclusion: Social interactions, particularly through the internet, collectively contributed to stock market participation. However, parental influence was less direct. Partners influenced primary market involvement through discussions. This provides novel insights into socio-cultural determinants of equity investing in an emerging South Asian context. Novelty: The study makes an original qualitative assessment of multiple social drivers on capital market engagement in Kathmandu Valley, adding new dimensions for understanding household finance decisions and developing inclusive capital markets.